The impact of oil industry-related social exclusion on community wellbeing and health in African countries - Nkem, Augusta C.; Topp, Stephanie M.; Devine, Sue; Li, Wendy Wen; Ogaji, Daprim Samuel (Frontiers in Public Health, 2022)
Background Oil is the mainstay revenue for a number of African countries. However, extraction can result in multiple impacts on the health and wellbeing of communities living in oil-rich areas. This review explored evidence of oil industry-related social exclusion on community health and wellbeing on the African continent. Methods We used a systematic approach guided by PRISMA to search six databases for empirical and descriptive sources focused on oil industry impacts, in any African country, between 1960 to 2021. Findings were grouped according to four dimensions of the Social Exclusion Knowledge Network (SEKN) framework: political, social, economic, and cultural. Results Fifteen articles were identified, of which 13 articles focused on Nigeria; while one focused on Sudan, and one on Côte d'Ivoire and South Africa. Evidence relating to political aspects of social exclusion encompassed marginalization of indigenous communities through land grabs and unequal representation in political decision making. Limited compensation for environmental damage and livelihood displacement caused by oil-extraction, and high rates of unemployment and poverty were key themes of the economic dimension. Evidence of social impacts included lack of government, or oil-industry investment in social infrastructure; poor health and wellbeing linked to land, air, and water pollution; homelessness and lack of social cohesion. The cultural dimension of social exclusion was comparatively underexplored and only six sources included data collection with indigenous residents, and comparatively more sources were written by non-citizens or non-residents of oil-industry affected areas. Major themes included impacts on collective identity, ways of life and values, particularly where loss of ownership or access to land was experienced. Conclusion Oil industry activities in African countries are clearly associated with multiple exclusionary impacts. However, the narrow body of empirical research limits understanding of the lived experiences and management of social exclusion by residents of oil-rich areas themselves and is an area deserving of further attention.